PENGARUH CUSTOMIZATION BASIC MARKET ORIENTATION DAN COMPETITIVE BENCHMARKING TERHADAP CUSTOMER RETENTION USAHA KECIL KNALPOT DI PURBALINGGA - Zulaicha, Ratni (Faculty of Economics and Business Universitas Jenderal Soedirman, 2011)
This research is entitled Ã¢â‚¬Å“The Effect of Customization Basic Market Orientation and Competitive Bencmarking Towards Customer Retention of Exhaust-Pipe Small Scale Usiness In PurbalinggaÃ¢â‚¬Â. The aims of research is to find out the variables that effect customer retention (repurchasing rate of return from the cunsumers as the result of consumers satisfaction). The variables include customization (the activities in setting customer oriented goals, identifying satisfaction opportunity available at the market, analyzing internal capability and formulating feasible strategies). Then basic market orientation (producerÃ¢â‚¬â„¢s perception towards sending time, pricing policy, promotion and understanding on cunsumer needs) and competitive benchmarking (producer perseption towards the process continuously in comparing the strategy, process and product of company with the other companies of organizations that have better performance, with the aim to study how they reach them and then reply the strategy into the company through making changes to conform with companyÃ¢â‚¬â„¢s condition). The method on analysis applied in this research is multiple linier regression analysis, Y = a1+bX1 + b2X2 + b3X3 then to test validity of variables it has used product moment correlation. As the result of F-test analysis, it has got the total effect of variables of customization (X1), basic orientation (X2) and competitive benchmarking (X3) towards customer retention (Y) that is 6.341. Whereas the result in partial through t-test, it has got that customization, basic market orientation and competitive benchmarking have an effect towards customer retention. Finally to find out the variable that has the most significant effect towards customer retention, it has used elasticity analysis and it shows that customization variable has the most significant effect towards customer retention that is 3.148. As conclusion of research is that customization, basic market orientation and competitive benchmarking whether in total or in partial have significant effect toward customer retention of exhaust pipe business in Purbalingga. Finally the implication of research mentions that it is better for the exhaust pipe businessmen in Purbalingga to produce the product suitable with consumers needs, plan new product, quarantee the product suitable with the standard and carry out a strict quality control.